COVID-19 vaccination in the mass vaccination center: clinical practice and effectiveness analysis - Fan, Jie; Zhu, Ling; Wu, Xiaohua; Luo, Chunyu; Huang, Ailong; Wang, Wei (Frontiers in Public Health, 2023)
Objectives: To gradually increase the vaccination rate among residents, the mass vaccination center for COVID-19 plays an important role. China began a nationwide COVID-19 vaccination drive in early March 2021. Here, we aimed to assess the opinions, experiences, and adverse events following immunization of the COVID-19 vaccination in the mass vaccination center in China. Methods: We describe the layout and functioning of Nan’an District mass vaccination center, the working mechanism, experience and effectiveness. Distribution of COVID-19 vaccine vaccination and adverse events following immunization reported in the mass vaccination center of Nan’an District were evaluated. Results: From 26 March 2021 to 28 April 2022, the mass vaccination center administered about 381,364 doses COVID-19 vaccine to the population. We observed a very low incidence of adverse events following immunization(AEFI)( 1.04/100 000). The chances of having AEFI were significantly higher in COVID-19 vaccine(CHO cell) than COVID-19 vaccine( Vero cell) (p = 0.046). Conclusion: The mass vaccination center was running successfully. It was effective and safe, providing vaccination services and increasing COVID-19 vaccination rates among the population.The experience of the mass vaccination center for COVID-19 in China could be shared by other areas currently providing immunization services against COVID-19.